Evaluation of Plasma-Assisted Noninvasive Surgery (PANIS) As a New Approach for Pterygium Removal with Amniotic Membrane Transplantation (AMT); a Clinical Case Series - Nejat, Farhad; Jadidi, Khosrow; Eghtedari, Shima; Nabavi, Nazanin Sadat; Moradi, Maryam (International Journal of Innovative Research in Medical Science, 2021)
Purpose: Medical plasma application has been used in different fields recently. In this study, we assess the outcome of using plasma-assisted noninvasive surgery (PANIS) with amniotic membrane transplantation (AMT) in pterygium surgical treatment. Methods: This clinical case series was conducted in 4 patients with primary grades 1, 2, and 3 pterygium (Table 1). After exclusion and inclusion criteria considerations, patients underwent different examinations. Various measurements were obtained such as uncorrected visual acuity (UCVA), refractive error (RE), the best-corrected visual acuity (BCVA), and ocular surface disease index (OSDI). The surgical procedure was pterygium removal from the cornea and then AMT attached to the conjunctival borders with plasma spots using a white handpiece of Plexr device (Plexr, GMV s.r.l Grottaferrata, Italy) instead (Table 2). After postoperative follow-ups within the first week of the surgery and in 1 month and 6 months later the results were obtained. Results: All patients have been fully recovered after the surgery without any complications. In all 4 cases, UCVA, BCVA, and RE parameters have improved during 6 months after the surgical procedure. Every patients’ OSDI decreased after the surgery. Recurrence has not been seen in any cases during 6 months follow-up. Conclusion: Pterygium removal surgery using the PANIS technique with AMT is safe, effective, fast, and cost-benefit.